Uncovering Indonesian Millennial's Halal Food Purchase Intention: Halal Value and Halal Logo as the Antecedents - Adila Sosianika; Fatya Alty Amalia (Jurnal Internasional Penelitian Bisnis Terapan, 2020)
This study attempts to uncover the Millennial’s decisional factors in purchase intention of Halal food in Indonesia, while heavily considering Halal food as a credence consumer good. After an analysis of 248 respondents using PLS-SEM, several interesting findings are obtained. Millennial’s understanding of Halal Value and Halal Logo serves as the antecedents of Purchase Intention of Halal food which is mediated by Attitude and Trust. Further analysis is also carried out herein by examining the moderating effect of gender with Multi-Group Analysis. For result, the distinct paths and significant difference of effects can be spot on the female and male group which shall provide deeper insights to any relevant stakeholders, especially food providers.